Optimization of Learning Through Edmodo-Based Hybrid Learning to Improve Learning Independence and Learning Outcomes - Kulsum, Umi (Universitas Negeri Makassar, 2020)
The study aims to determine the effectiveness of the use of Edmodo as a media study review of the learning outcomes; Knowing the learning independence relationship with learning outcomes and Knowing the influence of hybrid learning on learning independence and learning outcomes. This is experimental method with Non-Equivalent Control Group Design, consists of four groups of treatment with varied hybrid learning proportions, each 50% (meaning 50% learning hybrid learning and 50% face to face), 60% (meaning 60% of hybrid learning and 40% face to face), and 70% (meaning 70% hybrid learning and 30% face-to-face), and one group of others is a conventional group (only face to face), this group as a control group. Data Collection with questionnaires for learning independence and knowledge tests to determine learning achievement. The results showed: (1) the use of Edmodo was effective in enhancing the results of a larger experimental class learning compared to the control class so that learning became Optimal, (2) a significant relationship of learning independence learning with learning outcomes, significance 0.000, (3) there is a difference of influence of significant variation of hybrid learning to learning independence and learning outcomes, with significance 0,037